STRATEGI KEBERTAHANAN USAHA WARUNG KOPI TIKALA MANADO SUATU TINJAUAN ANTROPOLOGI - Damis, Mahyudin (HOLISTIK, Journal Of Social and Culture, 2018)
This study is intended to describe the strategy survive Tikala coffee shop manager in order to face the competition of business an increasingly tight coffee house in the city of Manado.This research method using qualitative research approaches with key informants consisting of managers, workers and customers. Data obtained from the informants with observation and in-depth interviews. While data on the development of business coffee house Tikala obtained with the method of the approach to history.The results of this research show that the strategy used by the surviving coffee shop manager Tikala using two strategies: to address production strategies on facets of the production on the one hand, and marketing strategies for addressing the problems of marketing itself on the other side.The strategy of holding out is part of the overall knowledge of the coffee shop manager Tikala looked at that side of production i.e. coffee drinks should be maintained his trademark, good taste or aroma must be the best and stay awake the quality as well as its traditional confectionary should also be tasty ? palatable. As for the sides of the game largely determined by the quality of the production of the good must be precisely maintained that when promoted confidence, either through the mass media as well as social media. By maintaining production quality then among the visitors ever sipping coffee in coffee shops has helped promote it through their personal social networks such as facebook, twitter, or blog-blog them so that coffee shop Tikala persist to this day.Keywords: Strategy, maintain, coffee house